Paper Waste as A Substrates for African Night Crawler (Eudrilus eugeniae) - Julian, Janice L.; Dalmacia, Francisca A.; Sigua, Loycel M.; Pugong, Desiry M.; Castañeto, Yolina T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
ABSTRACT   The increasing generation of paper waste presents significant environmental challenges. Vermicomposting offers a sustainable means of recycling biodegradable materials through earthworm activity. This study evaluated the growth, reproduction and vermicompost yield of the African Night Crawler (Eudrilus eugeniae) cultured on various paper waste substrates combined with manure. A Completely Randomized Design with six treatments and four replications was used: swine manure (control) and cow manure mixed with clean bond, used bond, notebook, carton, and newspaper wastes. Data on Eudrilus eugeniae proliferation, egg production, biomass, vermicompost yield, unconsumed substrate, and percent recovery were analyzed using ANOVA and Tukey’s HSD test at 5% significance (p < 0.05). Results showed that combining cow manure with paper wastes significantly improved E. eugeniae performance compared to the swine manure control(T1). E. eugeniae number increased from 112.25 (T1) to 808 (T5), egg production from 8.25 (T1) to 486 (T4), and vermicompost yield from 375 g (T1) to 1925 g (T4). Percent recovery peaked at 96.25% in T4, while unconsumed substrate was lowest (187.5 g). The carton and cow manure and newspaper and cow manure combinations yielded the best results, confirming their suitability as effective substrates for vermicomposting. The study concludes that cow manure-based mixtures, particularly with carton or used bond paper, provide optimal conditions for E. eugeniae and produce high-quality vermicompost. These findings highlight vermicomposting as a dual strategy for waste reduction and soil fertility improvement.